Factors affecting the implementation of green practices among traditional and complementary herbal-based entrepreneurs in Malaysia / Viduriati Sumin, Golnaz Rezai and Zainalabidin Mohamed - Sumin, Viduriati; Rezai, Golnaz; Mohamed, Zainalabidin (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
Environmental issues such as global warming, pollution, climate changes, deforestation, food safety, and an increasingly threatened biodiversity have emerged as new challenges to humans and the world ecosystem. All these factors have triggered awareness among all the players in the industries to implement green practices in their business activities. The implementation of green practices increases the value of products through the processing method of marketable, consumable, and used goods. At the same time, it is able to generate income and provide profit to the producer. This is especially applicable to those in the herbal industry which involves the use of natural treasures. Growing demand for herbal products and the lifestyle of today's health-conscious consumers have increased the production of herbal products in Malaysia. Thus, this has forced all Traditional and Complementary Herbal-Based (T&CH) entrepreneurs to move towards green technology practices. In fact, the global demand for herbal products is expected to increase up to USDS600 billion by 2020. This scenario has motivated T&CH entrepreneurs to produce herbal-based products in a sustainable or green way. This paper aims to assess T&CH entrepreneurs' perception and the factors that can influence their intention to implement green practices in their business activities. Two hundred and fifty-six respondents were interviewed for this study. Descriptive statistics and factor analysis were used to analyse the information on the T&CH entrepreneurs' perception towards going green. The results indicate that the major factors determining Malaysian T&CH entrepreneurs' intention towards going green are perceived relative advantage, complexity, attitude, subjective norms, perceived behavioural control and intention.